The Feminist Pioneer: Anna Raginsky and Her Impact on Canadian Jewish Activism - Barda, Kobby (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2023)
Anna Raginsky (1891-1981) was a transformative figure in Canadian Jewish activism. Raised in a family steeped in social causes, she became a leader in Zionist efforts at a young age. By 17, she held a leadership position in a Toronto Zionist council, and by 20, she was the first woman deputy president of the Toronto Zionist council. Throughout the 1920s and 1930s, Raginsky secured significant donations for pre-state Israel and championed groundbreaking projects. During World War II, her focus shifted to supporting European Jewry and the war effort. Her involvement in numerous organizations and lifelong commitment to Canadian Jewry and Israel cemented her place as a pioneer. Importantly, her leadership paved the way for a more prominent role for women in Canadian Jewish activism.